2017
DOI: 10.1016/j.xphs.2016.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Co-amorphous Formation Induced by Combination of Tranilast and Diphenhydramine Hydrochloride

Abstract: In this study, we investigated the formation of a co-amorphous system of tranilast (TRL) and diphenhydramine hydrochloride (DPH), which are drugs used for treating allergies and inflammation. The crystallization from undercooled melts of the drugs and drug mixtures was evaluated by thermal analysis. Both drugs in the amorphous state underwent crystallization on heating, although the mixture remained in the amorphous state, indicating the formation of a co-amorphous system. The physicochemical properties of co-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 40 publications
4
33
0
Order By: Relevance
“…In the coamorphous system, drug-drug or drug-excipient interacts with each other and inhibits crystallization at the amorphous state. 9,10) Several researchers have shown that a co-amorphous system improved stability of the amorphous state compared with that of single compound. 11,12) Hence SCL based on the co-amorphous approach, which stabilizes the thermodynamically unstable state by intermolecular interactions, should also improve the stability of the SCL state.…”
Section: Introductionmentioning
confidence: 99%
“…In the coamorphous system, drug-drug or drug-excipient interacts with each other and inhibits crystallization at the amorphous state. 9,10) Several researchers have shown that a co-amorphous system improved stability of the amorphous state compared with that of single compound. 11,12) Hence SCL based on the co-amorphous approach, which stabilizes the thermodynamically unstable state by intermolecular interactions, should also improve the stability of the SCL state.…”
Section: Introductionmentioning
confidence: 99%
“…Yamamura et al [ 32 , 33 , 34 ] suggested cimetidine as a carrier that forms dimeric co-amorphous mixtures with the acidic non-steroidal anti-inflammatory drugs (NSAID) naproxen, indomethacin, and diflunisal prepared by the solvent evaporation method, due to salt formation between the imidazole cimetidine ring and the carboxyl groups of the NSAIDs. Examples of investigated co-amorphous systems were: naproxen-cimetidine and indomethacin-ranitidine hydrochloride for relief of pain and of the gastrointestinal side effects of NSAIDs [ 15 , 17 ], simvastatin-glipizide for hypercholesterolemia and diabetes in metabolic disorders [ 24 ] and tranilast-diphenhydramine hydrochloride as anti-allergic/anti-inflammatory treatment [ 35 ]. Other studies showed that co-amorphous SDs increased the in vivo supersaturation and dissolution rate compared to individual amorphous or crystalline drugs but to a lesser extent than that expected from in vitro tests.…”
Section: Co-amorphous Dispersionsmentioning
confidence: 99%
“…For other molar ratios, it has been observed that the co-amorphous SDs recrystallize to pure components, with the excess component crystallizing faster [ 15 , 19 ], unless other mechanisms are involved [ 24 ]. However, there have also been studies [ 35 , 55 ] showing stability for other molecular proportions. For example, 2:1, 1:1 and 1:2 compositions of tranilast-diphenhydramine systems remained amorphous during 30 days and 1: 1 and 1:2 co-amorphous dispersions of IBU-ARG and IND-ARG did not crystallize, probably due to hydrogen bonding along with salt formation, which can explain the high stability of the 1:2 composition.…”
Section: Co-amorphous Dispersionsmentioning
confidence: 99%
“…If the API exhibits a low T g that results in poor stability, then a coformer should be chosen that will result in a higher T g for the coamorphous material (about 50 C above room temperature 27 ). The coamorphous T gmix can be estimated based on the Fox (see Possible Stabilizing Mechanisms) 76 or Gordon-Taylor 77,78 equation. Determining hydrogen bonding potential of potential coformers and the ability of a coamorphous system to disrupt crystalline dimers may also be useful.…”
Section: Coformer Selectionmentioning
confidence: 99%
“…Isothermal crystallization studies, such as those reported for ASDs and crystalline APIs, should be performed under various conditions for API and formulations to help understand and prevent crystallization. 76 API and formulation processing steps (such as drying, blending, compression, or film coating) need to be investigated for each system to determine crystallization tendencies and establish parameters to preserve the desired form.…”
Section: Stabilitymentioning
confidence: 99%